Molecular Chaperones, Cochaperones, and Ubiquitination/Deubiquitination System: Involvement in the Production of High Quality Spermatozoa - Meccariello, Rosaria (Hindawi Publishing Corporation, 2014)
Spermatogenesis is a complex process in which mitosis, meiosis, and cell differentiation events coexist. The need to guarantee the production of qualitatively functional spermatozoa has evolved into several control systems that check spermatogenesis progression/sperm maturation and tag aberrant gametes for degradation. In this review, we will focus on the importance of the evolutionarily conserved molecular pathways involving molecular chaperones belonging to the superfamily of heat shock proteins (HSPs), their cochaperones, and ubiquitination/deubiquitination system all over the spermatogenetic process. In this respect, we will discuss the conserved role played by the DNAJ protein Msj-1 (mouse sperm cell-specific DNAJ first homologue) and the deubiquitinating enzyme Ubpy (ubiquitin-specific processing protease-y) during the spermiogenesis in both mammals and nonmammalian vertebrates.